Subject Pools and Deception in Agricultural and Resource Economics Experiments - Cason, Timothy N.; Wu, Steven Y. (Environmental & resource economics, 2019)
The use of student subjects and deception in experiments are two controversial issues that often raise concerns among editors and reviewers, which might prevent quality research from being published in agricultural and resource economics (ARE) journals. We provide a self-contained methodological discussion of these issues. We argue that field professionals are the most appropriate subjects for questions related to policy or measurement, and students are the most appropriate subjects for scientific research questions closely tied to economic theory. Active deception, where subjects are provided with explicitly misleading information, has been avoided in the mainstream economics discipline because it can lead to a loss of experimental control, lead to subject selection bias, and impose negative externalities on other researchers. Disciplinary ARE journals may want to abide by these norms against deception to maintain credibility. Interdisciplinary ARE journals may have more flexibility, although it is important to provide guidelines to avoid too much reviewer-specific variation in standards. For ARE researchers, we suggest employing a deception-free experimental design whenever possible because we know of no field in which deception is encouraged.